Does an Insect's Unconditioned Response to Sucrose Reveal Expectations of Reward? - Gil, Mariana; Menzel, Randolf; De Marco, Rodrigo J. (PloS one, 2008)
We asked whether and how a sequence of a honeybee's experience with different reward magnitudes changes its subsequent unconditioned proboscis extension response (PER) to sucrose stimulation of the antennae, 24 hours after training, in the absence of reward, and under otherwise similar circumstances. We found that the bees that had experienced an increasing reward schedule extended their probosces earlier and during longer periods in comparison to bees that had experienced either decreasing or constant reward schedules, and that these effects at a later time depend upon the activation of memories formed on the basis of a specific property of the experienced reward, namely, that its magnitude increased over time. An anticipatory response to reward is typically thought of as being rooted in a subject's expectations of reward. Therefore our results make us wonder to what extent a long-term 'anticipatory' adjustment of a honeybee's PER is based upon an expectation of reward. Further experiments will aim to elucidate the neural substrates underlying reward anticipation in harnessed honeybees.